Congestion control protocol design based on delay parameters for layered multicast communication - BIAN Jing1; WANG Ze-qiang1; ZHANG Guang-zhao2; YANG Yi-qiang3 (Tongxin xuebao)
A congestion control mechanism,BDP（based on delay parameters） was presented to be used in receiver-driven layered multicast for multimedia transmission.Based on the dynamic varying of delay parameters,BDP can estimate the path’s available bandwidth for adaptive decision of layer join in order to provide guarantee of efficient network resources utilization,and can forecast the network congestion state in quick response to it.The ns2 simulation results show that BDP can achieve scalability,stability,fast convergence and be superior to MRAAR-MT protocol in TCP fairness.